THE AUDIT PROCESS IN COMPANIES THAT IMPLEMENT SOFTWARE ENGINEERING PROJECTS - Mellado, Rafael; Faúndez-Ugalde, Antonio; Blanco, María (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The use of technological resources and software has become standardized in today's society, which is why there is a need to be able to update according to the requirements that the market and industry demand from companies that develop products through a software engineering process. The role of the auditor is extremely important since he is the one who must make sure that everything is controlled and that the required needs are being fulfilled, as well as he is concerned about the security of the entities and their internal background. In this context, it is necessary to constantly improve the auditor's procedures and the legislation that regulates them, since the multiple frauds that companies suffer in terms of information obtained easily and quickly, without any major control, are well known, and it is here where care must be taken in order to reduce the levels of violations of access to unauthorized information assets. The objective of this paper is to present everything that surrounds the process of auditing requirements of software engineering projects, both generically and specifically in projects in particular the financial area, generally covering everything that is present in a software engineering project considering the need, what is obtained from them and why they arise in organizations.